2008
DOI: 10.3171/spi/2008/9/8/137
|View full text |Cite
|
Sign up to set email alerts
|

Single-level instrumented mini-open transforaminal lumbar interbody fusion in elderly patients

Abstract: Object The purpose of this study was to analyze the surgical outcomes in cases involving elderly patients who underwent single-level instrumented mini-open transforaminal lumbar interbody fusion (TLIF). Methods The authors performed a retrospective review of 27 consecutive cases involving elderly patients (≥ 65 years of age) who underwent single-level instrumented mini-open TLIF and were followed up for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 27 publications
7
48
1
Order By: Relevance
“…By way of historical comparison with traditional MIS TLIF, other studies have demonstrated 2°-3° of segmental correction in the sagittal plane. 15,21,23,48 In comparison with other forms of sagittal correction, historically MIS TLIF has shown only modest improvements in segmental lordotic angle. Additionally, the increase in segmental lordotic restoration in this study compares favorably to a weighted average increase of 3.9° published in a review by Uribe et al 43 Despite these positive findings, it is important to note that the question whether improvement in LL translates into actual improved clinical outcomes for treatment of spondylolisthesis has not been reliably answered in the literature.…”
Section: Key Resultsmentioning
confidence: 99%
“…By way of historical comparison with traditional MIS TLIF, other studies have demonstrated 2°-3° of segmental correction in the sagittal plane. 15,21,23,48 In comparison with other forms of sagittal correction, historically MIS TLIF has shown only modest improvements in segmental lordotic angle. Additionally, the increase in segmental lordotic restoration in this study compares favorably to a weighted average increase of 3.9° published in a review by Uribe et al 43 Despite these positive findings, it is important to note that the question whether improvement in LL translates into actual improved clinical outcomes for treatment of spondylolisthesis has not been reliably answered in the literature.…”
Section: Key Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][16][17][18] These objectives are achieved through conventional spinal approaches that involve the detachment of the paraspinal musculature, its denervation and devascularization, in addition to injury to the ligamentary structures, in contrast to minimally invasive techniques, which try to minimize the damage to these structures. Minimally invasive techniques are able to limit exposure as much as possible and to reduce the retraction of the structures, resulting in the less collateral damage to the tissues, a measurable reduction in morbidity, and above all, a more rapid functional recovery without departing from the primary objective established for spine surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies established a valid justification for this type of procedure in terms of their similar results in neurological outcomes and the preservation of structures that are essential to the biomechanics of the spine. [1][2][3][4][5][6][7][8][9][10][11][16][17][18] Minimally invasive approaches have been developed for degenerative, traumatic, and neoplastic pathologies, among others.…”
Section: -11mentioning
confidence: 99%
See 2 more Smart Citations